Nurse assistants’ experiences of encountering patients in grief due to the death of a loved one - a qualitative study in municipal health and social care - Anne-Lie Larsson; Ingela Beck; Ann-Christin Janlöv; Eva-Lena Einberg (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The aim was to explore nurse assistants´ experiences of paying attention to and encountering patients receiving municipal health and social care, who are in grief due to the death of a loved one. Methods A qualitative study with focus group interviews (n = 6) was conducted with nurse assistants (NAs) (n = 28) in municipal health and social care (n = 5) in southern Sweden. The data were analysed inductively using qualitative content analysis. Results Three categories (1) Noticing changes in the patient, (2) Using different strategies to create a dialogue with the patient, (3) Experiencing challenges when encountering patients in grief, included eight sub-categories were identified. The result is captured in the theme of Having to be attentive to signs of grief after patients´ loss of loved ones, sensing the right time to approach and comfort, while having to cope with emotional challenges. Conclusions The NAs encountered expressions of strong emotions from patients in grief, and even expressions of a desire to end their lives. Additionally, the NAs had to deal with their own emotions that were evoked when meeting patients in grief. These challenges indicate the need for enhanced conditions in the work culture, and improved training and supervision in health and social care.